Lipoma Masquerading as Soft Tissue Sarcoma: A Rare Case Report - Bhartiya, Richa; Mehra, Pallavi; Bariar, Naveen Kumar (Annals of Pathology and Laboratory Medicine, 2025)
Giant lipomas of the head and neck are rare benign tumors that can mimic soft tissue sarcomas. We report the case of a 38-year-old male who presented with a large 25x18 cm posterior neck mass associated with sinus and intermittent low-grade fever for ten days. Routine laboratory tests were normal. Ultrasonography showed a well-defined hypoechoic subcutaneous lesion without cystic areas or calcifications. FNAC demonstrated mature fat cells in strands of fibrous stroma, compatible with a lipoma. A contrast-enhanced CT scan showed no underlying bone or spinal involvement. The mass was surgically excised, and histopathology confirmed the benign diagnosis. No recurrence occurred on follow-up. This case underscores the importance of integrating cytology, imaging, and histopathology to differentiate giant lipomas from malignant tumors and guide clinical decision-making in such rare presentations.